Towards a determination of the physiological characteristics distinguishing successful mixed martial arts athletes: A systematic review of combat sport literature - James, L. P.; Haff, G. G.; Kelly, V. G.; Beckman, E. M. (Sports Medicine, 2016)
Background: Mixed martial arts (MMA) is a combat sport underpinned by techniques from other combat disciplines, in addition to strategies unique to the sport itself. These sports can be divided into two distinct categories (grappling or striking) based on differing technical demands. Uniquely, MMA combines both methods of combat and therefore appears to be physiologically complex requiring a spectrum of mechanical and metabolic qualities to drive performance. However, little is known about the physiological characteristics that distinguish higher- from lower-level MMA athletes. Such information provides guidance for training interventions, performance testing and talent identification. Furthermore, while MMA incorporates techniques from both grappling and striking sports, it is unknown precisely how these disciplines differ physiologically. Understanding the relationship between higher-level competitors in grappling and striking combat sports can provide further insight into the development of the optimal performance profile of a higher-level MMA athlete. Objective: This article aims to analyse the scientific literature on MMA and the primary combat sports underpinning it to determine the physiological adaptations that distinguish superior competitors, with a view to defining the optimal physiological profile for higher-level MMA performance. Furthermore, this article will explore the differences in these capabilities between grappling- and striking-based combat sports in the context of MMA. Methods: A literature search was undertaken via PubMed, Web of Science, SportDiscus and Google Scholar. The following sports were included for systematic review based on their relevance to MMA: mixed martial arts, boxing, Brazilian jiu-jitsu, judo, karate, kickboxing, Muay Thai and wrestling. The inclusion criteria allowed studies that compared athletes of differing competition levels in the same sport using a physiological performance measure. Only male, adult (aged 17-40 years), able-bodied competitors were included. The search history spanned from the earliest record until September 2015. Results: Of the eight combat sports searched for, five were represented across 23 studies. Sixteen investigations described maximal strength or neuromuscular power variables, while 19 articles reported anaerobic or aerobic measures. The results indicate that a number of strength, neuromuscular power and anaerobic variables distinguished higher- from lower-level combat sport athletes. However, these differences were less clear when groups were stratified within, rather than between competition grades. Greater aerobic power was generally not present amongst superior combat sport competitors. Conclusion: There appear to be differing physiological profiles between more successful grappling and striking combat sport athletes. This is represented by high-force demands of grappling sports causing an upwards shift of the entire force-velocity relationship driven by an increase in maximal strength. In comparison, smaller increases in maximal force production with more notable enhancements in lighter load, higher velocity actions may better identify superior performance in striking sports. Anaerobic capabilities largely distinguished higher- from lower-level combat sport athletes. In particular, longer-term anaerobic efforts seem to define successful grappling-based athletes, while superior competitors in striking sports tend to show dominance in shorter-term measures when compared with their lower-level counterparts. Given the demand for both forms of combat in MMA, a spectrum of physiological markers may characterize higher-level competitors. Furthermore, the performance profile of successful MMA athletes may differ based on combat sport history or competition strategy.